Leading Multicultural Teams. Case Study of XYZ. - Zemanová, Daniela (2016)
The main objective of the thesis is to analyze the topic of leading multicultural teams, with a specific attention to the particular example of the company XYZ; and answer the research questions with the gathered data and construct recommendations. The theoretical part provides a comprehensive overview of the concepts of multinational corporations, teams, multicultural teams and leadership. The assumptions derived from the theory serve as a base for the following empirical part, where the theoretical research is completed with a qualitative study. The qualitative study was conducted in cooperation with the company XYZ and professionals working directly in the multicultural teams were interviewed. By combining the findings from both theoretical and empirical part, many of the assumed benefits, especially the increased creativity, of the multicultural teams were confirmed. However, the negative aspects were identified as well, with the more difficult communication above all.